Older person's experiences of benefits gained from the support and advice given during preventive home visits. Issue 4 (30th October 2020) - Nivestam, Anna; Petersson, Pia; Westergren, Albert; Haak, Maria
Abstract : Background: Life expectancy is increasing all over the world. To be able to support this positive development, health interventions focusing on promotion and prevention are crucial. Preventive home visits represent one example of a health intervention which addresses both promotion through a supportive dialogue and prevention by giving advice. However, to give support and advice that older persons experience as beneficial, there is a need for more research. Aim: The aim of this study was to explore older person's experiences of the benefits gained from the support and advice given during the preventive home visit. Method: Individual semi‐structured interviews were conducted with 13 older persons, median age 77 years old, living at home, who had received a preventive home visit. The interviews were analysed with content analysis. Findings: The overarching theme Becoming empowered and recognised as a person was experienced as the major benefit of the support and advice given during the preventive home visit. The support and advice generated conditions for the person to become empowered, by contributing to a feeling of control and preparedness for the future. Furthermore, the support and advice given contributed to a feeling of becoming recognised as a person, as an outcome of the supportive dialogue and the assessment of their health, behaviour and their surrounding environment. Conclusion: The support and advice given during the preventive home visit were experienced as person‐centred, and conditions for becoming empowered were created. In order to create a positive outcome from the support and advice given during the preventive home visit, it seems important to focus on providing both a supportive dialogue and a structured assessment.